Distribution and stability of soil carbon in spekboom thicket, Eastern Cape, South Africa - Mchunu, Sinethemba Euginia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.